2020
DOI: 10.1002/mds.28045
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review of Brain Connectomics and Imaging to Improve Deep Brain Stimulation Outcomes

Abstract: A BS TRACT: DBS is an effective neuromodulatory therapy that has been applied in various conditions, including PD, essential tremor, dystonia, Tourette syndrome, and other movement disorders. There have also been recent examples of applications in epilepsy, chronic pain, and neuropsychiatric conditions. Innovations in neuroimaging technology have been driving connectomics, an emerging whole-brain network approach to neuroscience. Two rising techniques are functional connectivity profiling and structural connec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 77 publications
0
28
0
Order By: Relevance
“…STN‐GPi FC may thus offer promise as a biomarker for STN DBS responsiveness, used in conjunction with more established predictors such as levodopa responsiveness. Integration of this marker with other predictors of DBS responsiveness may be particularly powerful as a predictive tool in the clinical setting, as illustrated by the increased predictive power of the model using FC in addition to levodopa response compared with medication response alone 39 . However, this requires future prospective validation at the individual level, a promising approach undergoing development 40 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…STN‐GPi FC may thus offer promise as a biomarker for STN DBS responsiveness, used in conjunction with more established predictors such as levodopa responsiveness. Integration of this marker with other predictors of DBS responsiveness may be particularly powerful as a predictive tool in the clinical setting, as illustrated by the increased predictive power of the model using FC in addition to levodopa response compared with medication response alone 39 . However, this requires future prospective validation at the individual level, a promising approach undergoing development 40 …”
Section: Discussionmentioning
confidence: 99%
“…as illustrated by the increased predictive power of the model using FC in addition to levodopa response compared with medication response alone. 39 However, this requires future prospective validation at the individual level, a promising approach undergoing development. 40…”
Section: S T N D B S C O N N E C T I V I T Ymentioning
confidence: 99%
“…Use of normative functional MRI (fMRI) connectomes for stimulation and lesion network mapping is a commonly utilized technique to explore connections to a specific brain region of interest [8] , [9] . To examine functional connectivity to the stimulated area, the VTA was used as a seed region and resting-state fMRI data from 1,000 healthy subjects in the Brain Genomics Superstruct Project [10] were used to estimate functional connectivity to the remainder of the brain, as previously described [5] .…”
Section: Case Studymentioning
confidence: 99%
“…When correlating stimulation volume on GPi to clinical outcomes, in contrast to the axial subscore improvements, the overlap volume of VTA with GPi was not found significantly associated with improvement in camptocormia angles, which resembles recent findings that suggest the volume of VTA-GPi overlap may not positively related to outcomes of pallidal stimulation in dystonic symptoms 24 . Aside from its local effects on stimulated brain targets, DBS is also proposed to exert its therapeutic effect by modulating remote structures and the distributed brain networks 25 . In connectivity analysis, we found that the structural connectivity from VTA to right somatosensory cortex was significantly correlated with improvements in TCC angles, suggesting the role of somatosensory cortex and proprioceptive integration in mediating the effect of DBS treatment for camptocormia.…”
Section: Discussionmentioning
confidence: 99%